2003
DOI: 10.1046/j.1432-1033.2003.03880.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of a disulfide‐containing protein through a batch cell‐free system from wheat germ

Abstract: We have developed a highly productive cell-free protein synthesis system from wheat germ, which is expected to become an important tool for postgenomic research. However, this system has not been optimized for the synthesis of disulfide-containing proteins. Thus, we searched here for translation conditions under which a model protein, a single-chain antibody variable fragment (scFv), could be synthesized into its active form. Before the start of translation, the reducing agent dithiothreitol, which normally is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…The covalent assembled Fab and IgG concentrations was determined from the fraction of fully assembled antibody pixels under non-reducing conditions, relative to fully reduced HC, LC and clipped product bands that correspond to the soluble protein produced, as analyzed by autoradiography using a folding. 30,32,33 Indeed, previously reported yields of Fabs are less than 50 μg/mL, 37,38 or for an IgG ca. 1 μg/mL, 6 in E. coli based cell-free systems.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The covalent assembled Fab and IgG concentrations was determined from the fraction of fully assembled antibody pixels under non-reducing conditions, relative to fully reduced HC, LC and clipped product bands that correspond to the soluble protein produced, as analyzed by autoradiography using a folding. 30,32,33 Indeed, previously reported yields of Fabs are less than 50 μg/mL, 37,38 or for an IgG ca. 1 μg/mL, 6 in E. coli based cell-free systems.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the ability of E. coli to correctly fold recombinant proteins containing multiple disulfide bonds is limited, due the reducing environment of the cytosol and the limited capacity for co-translational folding. 10,[30][31][32][33][34] We used combinatorial optimization methods to rapidly and predictably optimize expression of a Fab that binds to the hIL-13 α1 receptor. 25 We optimized redox conditions with added glutathione buffers and disulfide isomerase chaperone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As reported, the existence of the intramolecular disulfide bond mainly influences the stability, folding, and functionality of the antibody fragment [48,49]. Until now, cell-free synthesis of functional proteins containing disulfide bonds was successfully performed using modified E. coli cell extracts [50][51][52][53][54][55][56], wheat germ extracts [57], and insect cell lysates [25,27,58]. Several publications have shown that the formation of disulfide bonds in E. coli cell lysates requires additional precautions.…”
Section: Cell-free Synthesis Of Proteins With Disulfide Bridges In Prmentioning
confidence: 99%
“…Initially, a scFv antibody fragment binding to Salmonella O-antigen was used as a model protein. Optimal reaction conditions were found when using a DTT-deficient wheat germ extract in combination with the addition of PDI, resulting in the synthesis of 13 µg of active scFv in a 1 mL batch reaction [9].…”
Section: Eukaryotic Cell-free Systemsmentioning
confidence: 99%
“…Over the last decade, cellfree systems have proven themselves as reliable, flexible and potent protein production platform, providing proteins of varying origins, classes and properties [3][4][5][6][7]. In particular, cell-free systems have been successfully used for the synthesis of antibodies and antibody fragments [8][9][10]. Since this class of molecules is highly in demand, this review aims to overview and summarize the advances made in the production of antibodies and antibody fragments in cell-free systems.…”
Section: Introductionmentioning
confidence: 99%